2013
DOI: 10.1021/jp405181u
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy and Time Resolved Optical Spectroscopy Study of the Electronic and Structural Interactions of ZnO Nanorods with Bovine Serum Albumin

Abstract: The adsorption behavior and electronic interactions of bovine serum albumin (BSA) with ZnO nanorod surfaces were investigated using high-resolution transmission electron microscopy as well as stationary and time-resolved optical spectroscopy techniques. Transmission electron microscopy shows that ZnO nanorod surfaces are surrounded by a homogeneous amorphous BSA film with thicknesses between ~2.5 and 5.0 nm. The electronic structure and adsorption geometry of BSA were examined using high-angle annular dark fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Klaumunzer et al reported on BSA adsorption on the ZnO nanostructures. Investigation of the structure properties with Transmission Electron Microscopy (TEM) showed the formation of an amorphous phase of BSA over well crystalline ZnO structure [82]. The study of the fundamental properties of ZnO nanostructures dipped into buffer solution with pH 7-7.3, showed a positive value of Z-potential for ZnO [83].…”
Section: Direct Immobilization Of Biomolecules On Top Of Zno Nanostrumentioning
confidence: 99%
See 2 more Smart Citations
“…Klaumunzer et al reported on BSA adsorption on the ZnO nanostructures. Investigation of the structure properties with Transmission Electron Microscopy (TEM) showed the formation of an amorphous phase of BSA over well crystalline ZnO structure [82]. The study of the fundamental properties of ZnO nanostructures dipped into buffer solution with pH 7-7.3, showed a positive value of Z-potential for ZnO [83].…”
Section: Direct Immobilization Of Biomolecules On Top Of Zno Nanostrumentioning
confidence: 99%
“…Due to their high surface/volume ratio, surface tailoring ability, novel electron transport properties and electronic conductance multifunctionality it is possible to successfully immobilize various types of biomolecules. Mostly nanorods (NRs) [36,38,40,43,45,47,48,53,56,74,82,86] and nanowires (NWs) [29,33,42,46,49,75,77,94] were used as a biosensor platform. Nanoparticles (NPs) [35,37,50,83,84,97,98], quantum dots [34,44], other low-dimentional structures [30,32,39,52,70,71,76,79,80,81,85,89,93,95,99] and thin films [31,51,72,73] ...…”
Section: Application Of Zno Nanostructures In Biosensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…26 The green PL emission around 560 nm is attributed to radiative recombination of a shallowly trapped electron and a deeply trapped hole. 27,28 The latter is ascribed to a doubly positively charged oxygen vacancy formed by hole trapping through a monovalent, positively charged oxygen vacancy at the surface of ZnO. [26][27][28] The orange emission (660 nm) of ZnO nanostructures may involve bulk defects associated with excess oxygen occupying interstitial lattice sites.…”
Section: Crystengcomm Papermentioning
confidence: 99%
“…27,28 The latter is ascribed to a doubly positively charged oxygen vacancy formed by hole trapping through a monovalent, positively charged oxygen vacancy at the surface of ZnO. [26][27][28] The orange emission (660 nm) of ZnO nanostructures may involve bulk defects associated with excess oxygen occupying interstitial lattice sites. 29 In any case, the bulk emission (393 nm, 660 nm) to surface emission (560 nm) intensity ratio is expected to crucially depend on both the size and morphology (surface to bulk ratio) and the surface coating of the ZnO mesocrystals.…”
Section: Crystengcomm Papermentioning
confidence: 99%